Hiding behind the keyboard : uncovering covert communication methods with forensic analysis - Shavers, Brett; Bair, John (Syngress, 2016)
Hiding Behind the Keyboard: Uncovering Covert Communication Methods with Forensic AnalysisiAexposes the latest electronic covert communication techniques used by cybercriminals, along with the needed investigative methods for identifying them. The book shows how to use the Internet for legitimate covert communication, while giving investigators the information they need for detecting cybercriminals who attempt to hide their true identity. Intended for practitioners and investigators, the book offers concrete examples on how to communicate securely, serving as an ideal reference for those who truly need protection, as well as those who investigate cybercriminals.